Pola air tersedia pada beberapa media tanam untuk tanaman strawberry (Fragaria Virginiana) - I Made Dwi Dharma Setiawan; Sumiyati Sumiyati; I Made Nada (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aims to determine water patterns available in different growing media. The study consisted of four treatments namely P1: rice husk charcoal media, P2: cocopeat and compost mix media with 2: 1 ratio, P3: soil and compost mix with 2: 1 ratio and P4: soil media. Field capacity for the entire treatment P1, P2, P3 and P4 from week 2 to week 12 in a row was 77,21% to 80,00%, 50,22% to 52,56%, 42,83% to 44,24%, and 36,70% to 37,95%. Temporary wilting point for all treatments P1, P2, P3 and P4 from week 2 to week 12 in a row was 36,59% to 18,99%, 29,09% and 10,63%, 10, 83% to 5,27% and 10,62% to 6,50%. Available water for strawberry plants for all treatments P1, P2, P3 and P4 from week 2 to week 12 in a row was 7,90 cm to 10,93 cm, 4,27 cm to 7,13 cm, 5,90 cm to 6,84 cm and 4,84 cm to 5,44 cm.